2017
DOI: 10.1063/1.4998945
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid laminated Timoshenko beam

Abstract: We consider the hybrid laminated Timoshenko beam model. This structure is given by two identical layers uniform on top of each other, taking into account that an adhesive of small thickness is bonding the two surfaces and produces an interfacial slip. We suppose that the beam is fastened securely on the left while on the right it’s free and has an attached container. Using the semigroup approach and a result of Borichev and Tomilov, we prove that the solution is polynomially stable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…Raposo [7] investigated a laminated Timoshenko beam with frictional damping, as modelled by the three equations, and proved that the system decays exponentially without the equal wave-speed condition (equation (4)). Recently, Raposo et al [8] considered a hybrid laminated Timoshenko beam. The authors proved that the solution is polynomially stable using the semigroup approach and a result of Borichev and Tomilov [9].…”
Section: Introductionmentioning
confidence: 99%
“…Raposo [7] investigated a laminated Timoshenko beam with frictional damping, as modelled by the three equations, and proved that the system decays exponentially without the equal wave-speed condition (equation (4)). Recently, Raposo et al [8] considered a hybrid laminated Timoshenko beam. The authors proved that the solution is polynomially stable using the semigroup approach and a result of Borichev and Tomilov [9].…”
Section: Introductionmentioning
confidence: 99%
“…Raposo (2016) proved that the exponential stability holds without any restriction on the parameters if the first two equations in (1.1) are also damped via frictional dampings. Recently, Raposo et al (2017) proved that, without any restriction on the parameters, the polynomial stability of (1.1) holds under additional three dynamic boundary conditions at l, where l is the length of the beam. For the stability of laminated beams with Cattaneo's or Fourier's type heat conduction, we refer the readers to Alves et al (2016) and Liu & Zhao (2017).…”
Section: Introductionmentioning
confidence: 99%
“…By adding suitable damping effects, such as internal damping, (boundary) frictional damping, and viscoelastic damping, it was shown that if the linear damping terms are added in two of the three equations, system (4) is exponentially stable under the "equal wave speeds" assumption (ρ/I ρ ) � (G/D). But if the damping terms are added in the three equations, then the system decays exponentially without the equal wave speeds assumption, see, for example, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. For thermoelastic laminated Timoshenko beam, there are few published works, we can mention the results due to Liu and Zhao [18] and Apalara [19].…”
Section: Introductionmentioning
confidence: 99%